STRATEGI PEMBELAJARAN HANDS-ON ACTIVITY: UPAYA MENGATASI KEJENUHAN BELAJAR DAN PENINGKATAN PARTISIPASI ABK DI PAUD - Maria Januarti; Vivit Diyah Anggraeni; Siti Muassaroh; Isnaini Utami; Endah Andayani (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2026)
ABSTRACT Hands-on activity is a learning approach that emphasizes students' active engagement through direct experience, exploration, and object manipulation, making learning more meaningful. This article aims to examine the implementation of the hands-on activity strategy in enhancing the active participation of Children with Special Needs (CSN) in Early Childhood Education (ECE). This study employed a literature review by analyzing 30 scientific articles published between 2021 and 2026 using four stages: identification, selection, analysis, and synthesis. The findings indicate that the hands-on activity strategy consistently improves learning motivation, reduces learning fatigue, and enhances the verbal and nonverbal participation of Children with Special Needs (CSN). In addition, this approach promotes cognitive, social, and motor development by providing learning experiences that accommodate learners' characteristics and individual needs. The review concludes that hands-on activity is an effective strategy for increasing the active participation of Children with Special Needs (CSN) while strengthening inclusive learning practices in Early Childhood Education. The primary contribution of this study is to provide a synthesis of empirical evidence that can serve as a reference for educators and researchers in developing experience-based inclusive learning. ABSTRAK Hands-on activity merupakan pendekatan pembelajaran yang menekankan keterlibatan aktif peserta didik melalui pengalaman langsung, eksplorasi, dan manipulasi objek sehingga pembelajaran menjadi lebih bermakna. Artikel ini bertujuan mengkaji implementasi strategi hands-on activity dalam meningkatkan partisipasi aktif Anak Berkebutuhan Khusus (ABK) di Pendidikan Anak Usia Dini (PAUD). Penelitian ini menggunakan metode kajian literatur (literature review) terhadap 30 artikel ilmiah yang dipublikasikan pada rentang tahun 2021–2026 melalui tahapan identifikasi, seleksi, analisis, dan sintesis. Hasil kajian menunjukkan bahwa strategi hands-on activity secara konsisten meningkatkan motivasi belajar, mengurangi kejenuhan, serta memperkuat partisipasi verbal dan nonverbal Anak Berkebutuhan Khusus (ABK). Selain itu, pendekatan ini mendukung perkembangan kognitif, sosial, dan motorik melalui pengalaman belajar yang sesuai dengan karakteristik dan kebutuhan peserta didik. Kajian ini menyimpulkan bahwa hands-on activity merupakan strategi yang efektif untuk meningkatkan partisipasi aktif Anak Berkebutuhan Khusus (ABK) sekaligus memperkuat praktik pembelajaran inklusif di PAUD. Kontribusi utama kajian ini adalah menyajikan sintesis bukti ilmiah yang dapat menjadi rujukan bagi pendidik dan peneliti dalam mengembangkan pembelajaran inklusif berbasis pengalaman langsung.